Analysis of Enoxaparin Effectiveness Based on COVID-19 Severity: A Study in a Secondary Hospital in Bandung, Indonesia - Budi Suprapti; Liana Debora; Dewi Kusumawati; Arina Dery PS; Gabriella Nathasya T; Mustika Novi Arini; Lusiana Dwi Aryanti (Indonesian Journal of Pharmacy, 2022)
Li Coagulopathy is a common predictor of mortality in COVID-19. Meanwhile, enoxaparin is an anticoagulant with anti-inflammatory, endothelial protection, and viral antagonist properties. Therefore, thromboprophylaxis with enoxaparin in COVID-19 is common in clinical settings. This study aims to assess enoxaparin's efficacy across different severity levels by examining its effect on primary outcomes comprising Length of stay (LOS), invasive mechanical ventilation, and mortality as well as secondary in the form of D-dimer, platelets, C-reactive protein (CRP), Neutrophil Lymphocyte Ratio (NLR), and Absolute Lymphocyte Count (ALC). During hospitalization, 269 patients received enoxaparin across varying severity levels comprising mild, moderate, and severe, while the Wilcoxon test was used to analyze the efficacy in each group. Additionally, the differences in patient characteristic profiles across the severity levels were determined using the Kruskal-Wallis test. The increase in mortality rate and the need for mechanical ventilation were directly proportional to the level of severity. D-dimer decreased from 1308.87 ng/ml to 979.83 ng/ml (p=<0,001) as well as from 1758.41 ng/ml to 1510.68 ng/ml (p=<0,001) in the mild and moderate levels respectively. The platelet increased from 225.65 to 369.39 x103/µl (p=<0,001) in mild and 256.77 to 398.97 x103/µl (p=<0,001) in moderate. Moreover, CRP improved in both mild 52.62 to 49.58 mg/l (p=0.031) and moderate 92.99 to 42.66 mg/l, (p=<0,001). Based on the results, enoxaparin effectively improves D-dimer, platelet, and CRP levels in mild and moderate but not in severe conditions, however, no effect was found on LOS, NLR, and ALC.